2001
DOI: 10.4315/0362-028x-64.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Variability Analysis of Bacterial Cross-Contamination Rates in Common Food Service Tasks

Abstract: This study investigated bacterial transfer rates between hands and other common surfaces involved in food preparation in the kitchen. Nalidixic acid-resistant Enterobacter aerogenes B199A was used as a surrogate microorganism to follow the cross-contamination events. Samples from at least 30 different participants were collected to determine the statistical distribution of each cross-contamination rate and to quantify the natural variability associated with that rate. The transfer rates among hands, foods, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(221 citation statements)
references
References 19 publications
7
203
1
7
Order By: Relevance
“…These two observations together suggest that hands are a reservoir of microorganisms and an important vehicle for their transfer to fresh produce during manual production, harvesting, and/or packing (32-34), common practices in produce production in this region (32). Though no other studies to date that we know of have quantified the relationships of microbes between hands and produce in the agricultural environment, this implication is consistent with those of other studies suggesting that hands are an important vehicle of contamination of produce (13,(33)(34)(35)(36). We hypothesize that microorganisms measured in our study could have been transferred either from hands to produce or produce to hands, as has been demonstrated to occur (33,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 80%
“…These two observations together suggest that hands are a reservoir of microorganisms and an important vehicle for their transfer to fresh produce during manual production, harvesting, and/or packing (32-34), common practices in produce production in this region (32). Though no other studies to date that we know of have quantified the relationships of microbes between hands and produce in the agricultural environment, this implication is consistent with those of other studies suggesting that hands are an important vehicle of contamination of produce (13,(33)(34)(35)(36). We hypothesize that microorganisms measured in our study could have been transferred either from hands to produce or produce to hands, as has been demonstrated to occur (33,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 80%
“…According to the World Health Organization [24], 25% of foodborne outbreaks are closely associated with cross-contamination events involving scarce hygiene practices, contaminated equipment, and contamination via food handlers, processing, or inadequate storage. Chen et al [25] demonstrated that bacterial transfer rates varied by more than five orders of magnitude depending on the nature of the surfaces involved in the cross-contamination. According to him a transfer rate of 100% was identified as the maximum value, although in some cases it was found that the recipients demonstrated higher numbers of microbial load than the contributor of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that various bacteria, including E. coli, S. aureus and Salmonella spp., can survive on human hands, sponges or cloths, utensils and currency for hours or days after initial contact (Scott and Bloomfield, 1990;Kusumaningrum et al, 2002). Other studies have quantified the extent of bacterial survival and cross-contamination between hands and various food items and kitchen surfaces (Zhaoet al, 1998;Chen et al, 2001;Montvilleet al, 2001). It became evident that quantifying the crosscontamination risk associated with various steps in the food preparation process can provide a scientific basis for risk management efforts in both the home and in food service.…”
Section: Comparison Of Domestic and Small-scale Kitchens In Terms Of mentioning
confidence: 99%